UTILIZATION OF SATELLITE IMEGERY FOR MAPPING SETTLEMENT DEVELOPMENT TRENDS IN THE CITY BUKITTINGGI - Sherena Aurelia Anwar; Ernawati Ernawati (Remote Sensing Technology Study Program, 2022)
This research was conducted to see the trend of the development of residential areas in the City of Bukittinggi using remote sensing methods. This technique is considered important and effective in providing spatial information on the earth's surface quickly, precisely and easily. This study aims to classify land use for residential areas using Landsat 8 OLI (Operational Land Imaginer) imagery. In this study, the maximum likelihood classification (MLC) method was used. The research used is descriptive with a quantitative approach, namely using numerical data, analysis, interpretation and presenting data in numerical form for sampling in identifying the results of land use for settlements in the City of Bukittinggi. The research results have changed in the last 5 years, it was found that there was an increase in residential areas of 7.92 ha in 2016 and 2021 using Landsat imagery. The results of the research in the form of a map are land use maps in the City of Bukittinggi to see the distribution of residential areas.